Pengaruh Volume Perdagangan dan Retum terhadap Bid-Ask Spread - Nico Yopida; Umi Murtini (Fakultas Bisnis UKDW, 2007)
Bid ask spread is afunction of three components which are; order processing, inventory holding, and informational asymmetry. Although holding cost and infurmational asymmetry can not be directly obsertted and needs a specific measurement, these two costs are interesting to be examined. The present paper aims to observe empirical evidences about the relationship between trade and return as a holding cost meaurernent for bid-ask spread. The samples are drawn -fro* companies listed on Jakarta Stock Exchange (JSE and included in rneasurement factors of ILQ-45 fro* January 2004 until December 2004. Using Error Correction Model (ECM), the result shows that the relationship between a trade volume series, return, and bid-ask spread are not either relatively or absolutely having a long-term equilibrium.Keywords : Bid-ask spread, return, statianary, co-integration.